2007
DOI: 10.1186/1471-2164-8-53
|View full text |Cite
|
Sign up to set email alerts
|

Combined array-comparative genomic hybridization and single-nucleotide polymorphism-loss of heterozygosity analysis reveals complex genetic alterations in cervical cancer

Abstract: Background: Cervical carcinoma develops as a result of multiple genetic alterations. Different studies investigated genomic alterations in cervical cancer mainly by means of metaphase comparative genomic hybridization (mCGH) and microsatellite marker analysis for the detection of loss of heterozygosity (LOH). Currently, high throughput methods such as array comparative genomic hybridization (array CGH), single nucleotide polymorphism array (SNP array) and gene expression arrays are available to study genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 61 publications
3
41
1
Order By: Relevance
“…Nevertheless, a rather poor correlation has been found between amplification and gene expression in this region, both in cell lines (22%) [16] and invasive tumors (18.9%) [22]. Although in the present study, a higher percentage of genes was deregulated (33.5%), a large proportion of the investigated genes was not deregulated.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, a rather poor correlation has been found between amplification and gene expression in this region, both in cell lines (22%) [16] and invasive tumors (18.9%) [22]. Although in the present study, a higher percentage of genes was deregulated (33.5%), a large proportion of the investigated genes was not deregulated.…”
Section: Discussioncontrasting
confidence: 80%
“…In cell lines having 5p amplified, only 22% of the investigated genes were upregulated. Similarly, invasive tumors or cell lines having amplified 3q showed even a lower proportion of upregulated genes [16]. The lack of correlation between copy number (CN) and gene expression [16], [31] suggests that some of the altered regions identified by SNP or mCGH arrays could be CN-altered discontinuously and not all genes within the regions are affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the aCGH illustrated that the chromosomal instability in tumors is more complicated than a simple deletion, duplication or translocation. This phenomenon of alternating multiple segmental deletions has been reported in other types of solid tumors [13-15]. The same is true for the deletions on chromosome 8q (8q24.12-qter) and 17p (17pter-p12) detected in our study as opposed to the duplications reported by Sowery et al We proceeded with a mutation assay of the TP53 gene located on chromosome 17p.…”
Section: Discussionsupporting
confidence: 87%
“…One study has found that SRC-3 levels are not differently expressed in healthy cervical tissue and cervical cancer, but SRC-3 expression has been correlated with lymph node involvement [74]. Moreover, the 20q12 genomic region encoding SRC-3 has been found to be amplified in cervical cancer cell lines, however, this would not correlate with an increase in SRC-3 mRNA expression [75]. …”
Section: Cervixmentioning
confidence: 99%